The experience of SENCOs in England during the COVID‐19 pandemic: the amplification and exposure of pre‐existing strengths and challenges and the prioritisation of mental health and wellbeing in schools. Issue 2 (27th December 2021) - Boddison, Adam; Curran, Helen
Abstract : A national survey of Special Educational Needs Coordinators (SENCOs) in England was conducted during the summer of 2020 in the midst of the global COVID‐19 pandemic. The annually conducted survey typically collates demographic data about the SENCO workforce, but given the wider context, this particular survey also included nine questions about SENCOs' experiences during the pandemic. More than 1000 SENCOs participated in the survey and the findings demonstrate the critical contribution of SENCOs in supporting pupils with SEND and maintaining effective communication with their families during the pandemic. The study provides evidence of an amplification effect in relation to the strengths and challenges that SENCOs had been experiencing prior to the pandemic. The study also demonstrates the importance of prioritising mental health and wellbeing in schools for both pupils and staff in the wake of the pandemic, with this being the key priority identified by SENCOs across all types of setting and all phases of education.